Processing and Characterization of High Density Polyethylene/Ethylene Vinyl Acetate Blends with Different VA Contents - Othman Y. Alothman (Advances in Materials Science and Engineering)
Different series of high density Polyethylene/Ethylene Vinyl Acetate (HDPE/EVA) blends were prepared via melt blending in a corotating intermeshing twin screw extruder. The effects of VA percentage and EVA loading ratio on the thermal, rheological viscoelastic, mechanical, and fracture toughness of the blends were analyzed. The results showed that the addition of EVA to HDPE reduces the thermal, elastic, and viscoelastic properties of the blends. The microscopic examination of the fracture surface confirmed the ductile fracture of HDPE/EVA blends for all blend ratios and VA percentages. Increasing the EVA ratio and VA content caused a significant reduction in the blend crystallinity but had no significant effect on melting temperature. The complex viscosity increased with increasing the percentage of EVA due to the restriction of molecular mobility and reduction of free volume, induced by the addition of EVA. The storage modulus decreased with increasing the EVA ratio and temperature, while it increased with increasing the frequency. Young’s modulus, yield strength, and fracture strain decreased with increasing the EVA ratio. Similarly, the fracture toughness decreased proportional to the EVA percentage. Finally the results indicated that the VA content has significant effects on the mechanical, thermal, and dynamic properties of HDPE/EVA blends.